A density functional theory investigation of the substituent effect on acyclovir and guanine derivatives for applications on energetic materials - Luciana Amorim da Silva; Gabriel Monteiro-de-Castro; Erick Braga Ferrão Galante; Itamar Borges Jr; Aline Cardoso Anastácio (Energetic Materials Frontiers)
The main challenge in designing new energetic materials is to find a good balance between four seemingly incompatible requirements, namely, high-energy content, low sensitivity, low production costs and less-polluting content. Fused nitrogen heterocycles of imidazole and pyrimidine, such as acyclovir and guanine, may offer interesting features due to the combination of a coplanar framework and a large conjugate system, which contribute to a reduced sensitivity, and a number of energetic bonds that can be increased by the introduction of explosophore substituents. In this work, to evaluate the potential of acyclovir and guanine derivatives as energetic materials, density functional theory (DFT) calculations were carried out to investigate the influence of the type and position of the explosophore substituent groups –NO2, –NHNO2, –N3, –ONO2, –CN, −N=N−, and −N=N(O)− on the energetic properties and chemical reactivity of 91 acyclovir- and guanine-based molecules, including thirty one nitramines, three nitroheterocycles, seventeen azides, seventeen nitrate esters, seventeen nitriles, three azo and three azoxy compounds. Several molecular properties were computed, including the chemical reactivity, the heat of formation and the detonation velocities and pressures using semiempirical equations. Among the molecules with no bridge groups, we found that, except for cyano group, position 4 were the most stable for acyclovir derivatives, whereas, except for the azido group, position 2 and 5 provided the most stable compounds for guanine derivatives. Among the bridged derivatives, depending on the molecule and positions, the nitrate esters and the nitro derivatives were more stable. In comparison with the parent compounds, calculations showed that the heat of formation (HOF) increased the most with azido and cyano groups, the density increased substantially with nitrate esters, nitro and nitramino groups, and the detonation velocities and pressures increased the most with nitrate ester, nitro and nitramino groups. Although azo groups resulted in higher HOFs than azoxy groups, azoxy derivatives showed superior values in terms of density, heat of maximum detonation, detonation velocity and pressure. Four nitrate esters (GD134, GD245, AZOXYGD13 and AZOXYGD25) displayed higher values of detonation velocity and pressure than RDX. The designed nitramines are less sensitive to impact than RDX. Except for GD134 and GD245, all guanine-based nitrate esters, with no bridge linkages, are expected to be less sensitive to impact than TNT. Due to the combination of good performance and stability, the compounds GD25, GD13, GD45, GD34, and GD14 have considerable potential as energetic materials. Therefore, their synthesis and further investigation are recommended.